Nationwide epidemiological study of tuberculosis and other respiratory pathogens among children and adolescents in Brazil: TBPed Brazil study protocol - Marcelo Comerlato Scotta; Márcia Polese-Bonatto; Fernanda Hammes Varela; Ivaine Tais Sauthier Sartor; Gabriela Oliveira Zavaglia; Caroline Nespolo de David; Ingrid Rodrigues Fernandes; Thais Raupp Azevedo; Annerose Barros; Anna Cristina C. Carvalho; Claudete Aparecida Araújo Cardoso; Clemax C. Sant’Anna; et al. (PLoS ONE, 2026)
The burden of lower respiratory tract infections (LRTIs) caused by Mycobacterium tuberculosis (MTB) among children and adolescents is often underestimated due to challenges in obtaining lower respiratory tract samples, nonspecific signs and symptoms, the paucibacillary nature of tuberculosis (TB), and the low yield of microbiological tests. Xpert MTB/RIF Ultra in induced sputum (IS) samples is the most promising test for improving microbiologic diagnosis of pulmonary tuberculosis (PTB) in young children. We describe the TBPed Brazil study, a multicenter, cross-sectional study in participants aged 6 months to 15 years. We designed a two-arm study: a hospital-based arm with patients hospitalized with LRTI and an outpatient-based arm with children and adolescents referred to TB-specialized clinics. The main aim in the hospital-based arm is to determine the prevalence of PTB. In the outpatient-based arm, the main objective is to determine the accuracy of Xpert MTB/RIF Ultra in IS samples compared to liquid culture. We evaluate in both arms: tuberculosis infection (TBI) prevalence, the accuracy of tongue swabs compared to liquid culture and clinical diagnosis, the risk factors associated with PTB or TBI; the accuracy of the Brazilian Ministry of Health scoring system for the diagnosis of PTB. In the hospital-based arm, we also evaluate the prevalence of viral and/or bacterial pathogens associated with LRTI. The sample size is 1,848 participants (1,118 hospitalized and 730 outpatients). Enrollment began in December 2021 and is expected to conclude in 2026, involving 27 study sites across Brazil. This is the first prospective nationwide investigation into the prevalence of PTB and TBI, as well as diagnostic accuracy across different methods, in children and adolescents in a large country with a significant TB burden. Study results will provide critical data on epidemiological, clinical, and diagnostic approaches to MTB and other respiratory pathogens in children in Brazil, guiding future studies and public health policies.